Channels and policy debate in the globalization-inequality-poverty nexus - Machiko Nissanke; Erik Thorbecke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The paper offers a critical literature review of the debate surrounding the globalizationpoverty nexus, focusing on channels and linkages through which globalization affects the poor. After introducing four different concepts used to measure trends in world income inequality, it examines first the `growth' conduit through which globalization affects poverty. Treating inequality as the explicit filter between growth and poverty reduction, the causal chain of openness-growth-inequality-poverty is scrutinized, link by link. The paper then moves on to examine other channels in the globalization-poverty nexus that operate through changes in relative factor and good prices, factor movements, the nature of technological change and diffusion, the impact of globalization on volatility and vulnerability, the worldwide flow of information, global disinflation, and institutions, respectively. The paper concludes with a discussion of strategic policy issues within the context of the globalization debate.
Keywords: F0; I3; O1; 330; globalization; growth; inequality; poverty; Globalisierung; Armut; Einkommensverteilung; Wirtschaftswachstum